DETERMINANT OF ELDERLY POSYANDU UTILIZATION IN WORKING AREAS OF SIX PUBLIC HEALTH CENTERS (PUSKESMAS) OF SEMARANG CITY - Arum Prihatiningsih; Ayun Sriatmi; Eka Yunila Fatmasari (Poltekkes Kemenkes Semarang, 2020)
In improving the total coverage of elderly healthcare, public health centers (puskesmas) provide services off-building, one of which is elderly posyandu. In Semarang city, the average elderly attendance rate to posyandu was still meager. It impacted healthcare's low coverage and decreased elderlies' health status quality. This study aimed to analyze factors affecting the elderly posyandu utilization in working areas of six puskesmas of Semarang city. This study was quantitative with a cross-sectional design. The population was 42.679 elderlies with 70 elderly samples. The sampling technique was accidental sampling using questionnaires. The univariate analysis used a frequency distribution, while the relationship analysis used the rank spearman test. The study results showed relationships of attitude (p= 0.048), trust (p= 0.000), access (p= 0.000), cadres role (p=0.000), healthcare workers role (p=0.000), family support (p=0.015), facility (p=0.000), and disease susceptibility perception (0.002) to elderly posyandu utilization in working areas of six puskesmas of Semarang city. It is necessary to maximize funding for activities and facilities, innovate the development of gymnastics, conduct a singing together activity, and provide an understanding of disease risk factors.